Mesoporous ferroferric oxide composite material with three-dimensional sandwich double-coated carbon net encapsulated and hydrogenated titanium dioxide coated core-shell structure as well as preparation method and application of mesoporous ferroferric oxide composite material

By using a three-dimensional sandwiched double-clad carbon mesh encapsulated hydrogenated titanium dioxide-clad core-shell structure mesoporous ferrotetraoxide composite material, the problem of volume expansion of the negative electrode material of lithium-ion battery during charging and discharging is solved, and efficient electrochemical performance and long-cycle capability are achieved.

CN119503894APending Publication Date: 2025-02-25YANGZHOU POLYTECHNIC INST
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411720815.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The volume expansion problem of existing lithium-ion battery negative electrode materials during charging and discharging results in unstable battery performance and making it difficult to achieve long cycles with high specific capacity.

Method used

The preparation method of a three-dimensional sandwiched double-clad carbon mesh encapsulated hydrogenated titanium dioxide-clad core-shell structure mesoporous ferrous oxide composite material is used to inhibit the volume expansion of ferrous oxide and improve the conductivity through multi-layered coating structure and hydrogenation treatment.

Benefits of technology

It effectively suppresses the volume expansion of iron tetroxide during charging and discharging, improves the cycling performance and conductivity of the battery, and expands the application of materials in the fields of energy storage and semiconductors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503894A_ABST
    Figure CN119503894A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a three-dimensional sandwich double-coated carbon net packaged hydrogenated titanium dioxide coated core-shell structure mesoporous ferroferric oxide composite material in the technical field of preparation of a lithium battery negative electrode material, aiming at the problem that a metal oxide ferroferric oxide serving as the lithium battery negative electrode material is easy to crack in structure during charging and discharging, and discloses the preparation method and application of the three-dimensional sandwich double-coated carbon net packaged hydrogenated titanium dioxide coated core-shell structure mesoporous ferroferric oxide composite material in the technical field of preparation of the lithium battery negative electrode material. Comprising the following steps: S1, preparing mesoporous ferroferric oxide nanoparticles; s2, preparing the carbon coated mesoporous ferroferric oxide nano particles; s3, preparing ferroferric oxide with a porous core-shell structure coated with titanium dioxide; s4, preparation of ferroferric oxide with a porous core-shell structure coated with hydrogenated titanium dioxide; s5, carbon net packaging and hydrogenated titanium dioxide coating porous core-shell structure ferroferric oxide; the nano composite material prepared by the invention has the characteristics of regular morphology, high electrochemical performance, stable charge and discharge performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery negative electrode material preparation, and in particular to a method for preparing a ferrosoferric oxide composite material. Background Art

[0002] At present, there are various types of negative electrodes for lithium-ion batteries, among which transition metal oxides are a type of negative electrode material with great potential. Due to their unique properties such as good ferroelectricity, superconductivity, piezoelectricity and magnetoelasticity, they have broad application prospects in energy storage, energy conversion, solar devices and semiconductors. Titanium dioxide (TiO2) and carbon are often used as auxiliary materials to modify the surface stability and conductivity of transition metal oxide materials, thereby obtaining new nanocomposites containing titanium dioxide and carbon, which have broad application prospects in electronics, batteries, catalysts, biomedicine, radio waves and other fields.

[0003] However, currently, transition metals are usually coated with a single TiO2 or carbon, and the conductivity of TiO2 itself is poor; the single-layer carbon coating cannot effectively inhibit the volume expansion of Fe3O4 nanoparticles during the battery cycle, resulting in the battery performance being unable to be cycled for a long time at a high specific capacity. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material, its preparation method and application. The prepared nanoparticles have the characteristics of regular morphology, good uniformity and high electrochemical performance.

[0005] The object of the present invention is achieved by: a method for preparing a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material, comprising the following steps: S1, adding iron salt, ammonium carbonate, ammonium bicarbonate, ammonium chloride and hexamethylenetetramine to ethylene glycol solution, stirring to obtain turbid liquid A, and then transferring to a reactor for hydrothermal reaction to obtain black powder B; S2, calcining the black powder B in a tube furnace under a nitrogen atmosphere to obtain mesoporous Fe3O4 nanoparticles; S3, adding mesoporous ferroferric oxide nanoparticles to a mixed solution of anhydrous ethanol and deionized water, stirring to make them evenly dispersed; then adding ammonia water, formaldehyde and resorcinol, stirring to obtain a mixed solution B; transferring to a reactor for hydrothermal reaction to obtain carbon-coated core-shell structured mesoporous ferroferric oxide nanoparticles; S4, adding carbon-coated core-shell structured mesoporous ferroferric oxide nanoparticles into an anhydrous ethanol solution, stirring to obtain a mixed solution C, then adding tetrabutyl titanate, stirring in a water bath to obtain a titanium dioxide-encapsulated carbon-coated core-shell structured mesoporous ferroferric oxide composite material; S5, adding the titanium dioxide encapsulated carbon-coated core-shell structure mesoporous ferrosoferric oxide composite material to a sodium hydroxide solution, stirring, then slowly adding a hydrochloric acid solution until no bubbles are generated, stirring and filtering to obtain a solid powder D; S6, placing the solid powder D in a tube furnace, and calcining it in a hydrogen-argon atmosphere to obtain a sandwich structure hydrogenated titanium dioxide-coated core-shell mesoporous ferrosoferric oxide composite material; S7. Grind the sandwich structure hydrogenated titanium dioxide coated core-shell mesoporous ferroferric oxide composite material and glucose, place them in a tubular furnace, and calcine them in a high-purity argon atmosphere to obtain a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferroferric oxide composite material.

[0006] Furthermore, the iron salt in S1 is ferric chloride, ferric chloride hexahydrate or ferrous sulfate, the mass ratio of the iron salt to ammonium carbonate, ammonium bicarbonate, ammonium chloride and hexamethylenetetramine is 4-6:1:1:1:2, the hydrothermal temperature is 200°C, and the hydrothermal time is 24h.

[0007] Furthermore, the calcination temperature in S2 is 500°C, the heating rate from room temperature to 300°C is 3°C / min, the calcination is 2 h, the heating rate from 300°C to 500°C is 10°C / min, and the calcination time is 2 h.

[0008] Furthermore, the volume ratio of anhydrous ethanol to deionized water in S3 is 1:1; the molar ratio of ammonia water, formaldehyde and resorcinol to mesoporous ferrosoferric oxide nanoparticles is 0.1:0.1:0.2:2.

[0009] Furthermore, the volume ratio of the mixed solution C of S4 to tetrabutyl titanate is 10:1, the water bath temperature is 55° C., and the water bath time is 24 h.

[0010] Furthermore, the sodium hydroxide concentration in S5 is 2 M, the stirring time is 2 h, and the hydrochloric acid concentration is 0.2 M.

[0011] Furthermore, in S6, the calcination temperature is 450° C., the heating rate is 5° C. / min, and the calcination is performed for 4 h.

[0012] Furthermore, the mass ratio of the sandwich structure hydrogenated titanium dioxide-coated core-shell mesoporous ferrosoferric oxide composite material to glucose in S7 is 4:1, the calcination atmosphere is high-purity nitrogen, the calcination temperature is 500°C, the heating rate is 3°C / min, and the calcination is 4h.

[0013] A three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material prepared by the preparation method.

[0014] Application of a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material in the preparation of lithium-ion battery negative electrode materials.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention obtains a double coating layer with a mesoporous structure of ferroferric oxide as the core and a carbon layer and a titanium dioxide layer as the coating layer to inhibit the volume expansion of ferroferric oxide during the charging and discharging process. The presence of the mesoporous structure can relieve the volume stress of ferroferric oxide during the charging and discharging process, and the double coating layer can structurally inhibit the volume expansion of ferroferric oxide during the charging and discharging process. At the same time, the titanium dioxide is hydrogenated to improve the conductivity of the material.

[0016] On this basis, a three-dimensional carbon network is introduced on the surface of the composite material through simple grinding and calcination, providing transmission channels for electrons and lithium ions, further improving the conductivity while improving the mobility of lithium ions and inhibiting the volume expansion of ferroferric oxide, thereby expanding the application of the composite material in the fields of energy storage and semiconductors; the three-dimensional carbon network can improve the conductivity and the mobility of lithium ions, and the double-coated layer of hydrogenated titanium dioxide and carbon layer can inhibit the volume expansion of ferroferric oxide during the charge and discharge behavior; the preparation process of the invention is easy to control, the process is simple, the cost is low, and it is suitable for industrial mass production; the prepared nanocomposite material has the characteristics of regular morphology, good uniformity, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0018] Figure 1 This is a TEM image of the mesoporous ferrosoferric oxide of the present invention.

[0019] Figure 2 This is a TEM image of the carbon-coated core-shell structured mesoporous ferrosoferric oxide of the present invention.

[0020] Figure 3 This is a TEM image of the double-coated hydrogenated titanium dioxide core-shell structure mesoporous ferrosoferric oxide of the present invention.

[0021] Figure 4This is a TEM image of the three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide of the present invention.

[0022] Figure 5 This is a SEM image of the mesoporous ferrosoferric oxide of the present invention.

[0023] Figure 6 This is a SEM image of the carbon-coated core-shell structured mesoporous ferrosoferric oxide of the present invention.

[0024] Figure 7 This is a SEM image of the double-coated hydrogenated titanium dioxide core-shell structure mesoporous ferrosoferric oxide of the present invention.

[0025] Figure 8 This is a SEM image of the three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide of the present invention.

[0026] Fig. 9 This is the cycling performance diagram of the core-shell structured mesoporous ferrosoferric oxide encapsulated with hydrogenated titanium dioxide and coated with a 3D sandwich double-coated carbon mesh as the anode material for a half-cell button-type lithium-ion battery.

[0027] Fig.10 This is a SEM image of a three-dimensional sandwich double-coated carbon mesh encapsulating hydrogenated titanium dioxide-coated core-shell structured mesoporous ferrosoferric oxide according to Example 2 of the present invention.

[0028] Fig.11 This is a SEM image of the three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide in Example 3 of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1.

[0031] A method for preparing a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide, comprising the following steps: S1. Add 1.8 g of ferric chloride, 0.3 g of ammonium carbonate, 0.3 g of ammonium bicarbonate, 0.3 g of ammonium chloride and 0.6 g of hexamethylenetetramine into 90 mL of ethylene glycol solution to dissolve to obtain an iron ion solution A; subject the iron ion solution to a hydrothermal reaction at 200 °C for 20 h, then filter, wash the filter cake with water and ethanol by centrifugation, respectively, and then dry the filter cake to obtain a black solid powder B.

[0032] S2. Place the black solid powder B in a tubular furnace and calcine it in a nitrogen atmosphere at a calcination temperature of 500 °C, a heating rate of 3 °C / min from room temperature to 300 °C, calcination for 2 h, a heating rate of 10 °C / min from 300 °C to 500 °C, and a calcination time of 2 h to obtain a mesoporous structured ferrosoferric oxide nanomaterial.

[0033] S3. Add 1 g of mesoporous ferroferric oxide nanoparticles into a mixed solution of 90 mL of deionized water and anhydrous ethanol (15 mL:15 mL), and stir magnetically for 40 min. Then, add 0.1 mL of 28% ammonia water, 2 mL of formaldehyde and 0.8 g of resorcinol, and stir for 30 min to obtain a mixed solution. The mixed solution is hydrothermally reacted at 100 °C for 24 h, and then filtered. The filter cake is washed by centrifugation with water and ethanol, respectively, and then the filter cake is dried to obtain a single-layer carbon-coated core-shell structured ferroferric oxide composite material.

[0034] S4. Add the carbon-coated core-shell structured ferroferric oxide composite material into 100 mL of anhydrous ethanol solution and stir to obtain a mixed solution C; add 10 mL of tetrabutyl titanate to the mixed solution C, set the water bath temperature to 55°C, stir for 24 h, and then filter, wash the filter cake by centrifugation with water and ethanol respectively, and then dry the filter cake to obtain a core-shell structured mesoporous ferroferric oxide nanocomposite material wrapped with a double layer of titanium dioxide and carbon.

[0035] S5. Add the core-shell structured mesoporous ferrosoferric oxide composite material wrapped by titanium dioxide and carbon double layer into 150 mL of 2 M sodium hydroxide solution, stir evenly, and slowly add 0.2 M hydrochloric acid solution until no bubbles are generated. Filter, wash the filter cake by centrifugation with water and ethanol respectively, and then dry the filter cake to obtain solid D.

[0036] S6. Place solid D in a tube furnace and calcine it in a hydrogen-argon atmosphere (volume ratio of 1:19) at a temperature of 450 °C, a heating rate of 5 °C / min, and calcine for 4 h. A sandwich double-coated hydrogenated titanium dioxide core-shell structured mesoporous ferrosoferric oxide composite material is obtained.

[0037] S7. Grind 2 g of sandwich double-coated hydrogenated titanium dioxide core-shell structure mesoporous ferroferric oxide composite material and 0.5 g of glucose in a grinder to obtain a mixed powder. Place the mixed powder in a tubular furnace and calcine it in a high-purity argon atmosphere at a calcination temperature of 500°C and a heating rate of 3°C / min for 4 h to obtain a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferroferric oxide composite material.

[0038] Reference Figure 1-4 , which are TEM images of mesoporous ferroferric oxide, carbon-coated core-shell mesoporous ferroferric oxide, double-coated hydrogenated titanium dioxide core-shell mesoporous ferroferric oxide, and three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide core-shell mesoporous ferroferric oxide. It can be seen from the figure that the mesoporous ferroferric oxide is a spherical structure with pores of different sizes inside. The method of the present invention can successfully prepare mesoporous ferroferric oxide of different sizes, which can not only relieve the volume stress of ferroferric oxide, but also provide reaction sites (CO chemical bonds) for the subsequent carbon coating. The carbon-coated core-shell structure mesoporous ferroferric oxide composite material can clearly see that the mesoporous ferroferric oxide is coated on 10 The carbon layer with a thickness of about nm can inhibit the volume expansion of ferroferric oxide during the charging and discharging process; the double-coated hydrogenated titanium dioxide core-shell structure mesoporous ferroferric oxide composite material can clearly see that the hydrogenated titanium dioxide layer encapsulates the carbon-coated core-shell mesoporous ferroferric oxide inside, which can greatly alleviate the volume expansion of ferroferric oxide and improve the cycle performance of the electrode material; the surface of the three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferroferric oxide material is covered with a "spider web"-like carbon layer. The carbon mesh not only provides three-dimensional electron and ion channels for the composite material, but also assists the hydrogenated titanium dioxide layer and the carbon layer to inhibit the volume expansion of ferroferric oxide.

[0039] Reference Figure 5-8 , respectively, are SEM images of mesoporous ferric oxide, carbon-coated core-shell mesoporous ferric oxide, double-coated hydrogenated titanium dioxide core-shell mesoporous ferric oxide, and three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell mesoporous ferric oxide. From the figure, the structural morphology corresponds to the reference Figure 1-4 The conclusions are similar.

[0040] The three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide-coated core-shell structure mesoporous ferrosoferric oxide composite material prepared above is used as a half-cell button-type lithium ion anode material.

[0041] Preparation process: First, prepare a slurry bottle, add 1 mL of N-methyl-2-pyrrolidone (NMP) organic solvent, 20 mg of polyvinylidene fluoride, and 20 mg of conductive carbon black in turn, stir thoroughly for about 20 min, then add 160 mg of fully ground active material three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferroferric oxide composite material to the slurry bottle, stir for 24 h, use a coater to apply the prepared slurry on the copper foil with a thickness of 60 mm, and vacuum dry the copper foil for 8 h. Subsequently, the copper foil was cut into coin-sized electrode sheets, and the mass of active material on a single electrode was weighed. Finally, the CR2032 button battery was installed in the argon-filled glove box in the assembly order of the button battery, in which the electrolyte used was 1M LiPF6, and it was left to stand for 24 h, and then the corresponding test was carried out.

[0042] Test method: Use Xinwei CT-4008 battery tester, voltage range is 0.01~3.00 V, current density is 0.2 A g -1 Conduct electrochemical performance tests. Fig. 9 It can be found that the capacity of the three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferroferric oxide composite material as a lithium-ion half-battery negative electrode material after 300 cycles is 589.34 mAh g -1 , indicating that the carbon network, hydrogenated titanium dioxide and carbon layer effectively inhibited the volume expansion of ferroferric oxide during battery cycling and improved its conductivity.

[0043] Embodiment 2: The 1.8 g of ferric chloride in Example 1 was replaced with 1.8 g of ferric chloride hexahydrate, and the remaining steps were the same as in Example 1 to prepare a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide.

[0044] Embodiment 3: The 1.8 g of ferric chloride in Example 1 was replaced with 1.8 g of ferrous sulfate, and the remaining steps were the same as in Example 1 to prepare a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide.

[0045] Fig.10 and Fig.11 The SEM images of the nanoparticles of Example 2 and Example 3 respectively show that a three-dimensional sandwich double-coated carbon mesh-encapsulated hydrogenated titanium dioxide-coated core-shell structured mesoporous ferrosoferric oxide nanocomposite material was prepared.

[0046] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material, characterized in that: The following steps are involved: S1, adding iron salt, ammonium carbonate, ammonium bicarbonate, ammonium chloride and hexamethylenetetramine to ethylene glycol solution, stirring to obtain turbid liquid A, and then transferring to a reactor for hydrothermal reaction to obtain black powder B; S2, calcining the black powder B in a tube furnace under a nitrogen atmosphere to obtain mesoporous Fe3O4 nanoparticles; S3, adding mesoporous ferroferric oxide nanoparticles to a mixed solution of anhydrous ethanol and deionized water, stirring to make them evenly dispersed; then adding ammonia water, formaldehyde and resorcinol, stirring to obtain a mixed solution B; transferring to a reactor for hydrothermal reaction to obtain carbon-coated core-shell structured mesoporous ferroferric oxide nanoparticles; S4, adding carbon-coated core-shell structured mesoporous ferroferric oxide nanoparticles into an anhydrous ethanol solution, stirring to obtain a mixed solution C, then adding tetrabutyl titanate, stirring in a water bath to obtain a titanium dioxide-encapsulated carbon-coated core-shell structured mesoporous ferroferric oxide composite material; S5, adding the titanium dioxide encapsulated carbon-coated core-shell structure mesoporous ferrosoferric oxide composite material to a sodium hydroxide solution, stirring, then slowly adding a hydrochloric acid solution until no bubbles are generated, stirring and filtering to obtain a solid powder D; S6, placing the solid powder D in a tube furnace, and calcining it in a hydrogen-argon atmosphere to obtain a sandwich structure hydrogenated titanium dioxide-coated core-shell mesoporous ferrosoferric oxide composite material; S7. Grind the sandwich structure hydrogenated titanium dioxide coated core-shell mesoporous ferroferric oxide composite material and glucose, place them in a tubular furnace, and calcine them in a high-purity argon atmosphere to obtain a three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferroferric oxide composite material.

2. The method for preparing the three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material according to claim 1, characterized in that: The iron salt in S1 is ferric chloride, ferric chloride hexahydrate or ferrous sulfate, the mass ratio of the iron salt to ammonium carbonate, ammonium bicarbonate, ammonium chloride and hexamethylenetetramine is 4-6:1:1:1:2, the hydrothermal temperature is 200°C, and the hydrothermal time is 24h.

3. The method for preparing the three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material according to claim 1, characterized in that: The calcination temperature in S2 is 500°C, the heating rate from room temperature to 300°C is 3°C / min, the calcination is for 2 h, the heating rate from 300°C to 500°C is 10°C / min, and the calcination time is 2 h.

4. The three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material according to claim 1, characterized in that: The volume ratio of anhydrous ethanol to deionized water in S3 is 1:1; the molar ratio of ammonia water, formaldehyde and resorcinol to mesoporous ferrosoferric oxide nanoparticles is 0.1:0.1:0.2:

2.

5. The three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material according to claim 1, characterized in that: The volume ratio of the mixed solution C of S4 to tetrabutyl titanate is 10:1, the water bath temperature is 55° C., and the water bath time is 24 h.

6. The three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material according to claim 1, characterized in that: The sodium hydroxide concentration in S5 is 2 M, the stirring time is 2 h, and the hydrochloric acid concentration is 0.2 M.

7. The three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material according to claim 1, characterized in that: In the S6, the calcination temperature is 450° C., the heating rate is 5° C. / min, and the calcination is performed for 4 hours.

8. The three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material according to claim 1, characterized in that: The mass ratio of the sandwich structure hydrogenated titanium dioxide-coated core-shell mesoporous ferrosoferric oxide composite material in S7 to glucose is 4:1, the calcination atmosphere is high-purity nitrogen, the calcination temperature is 500°C, the heating rate is 3°C / min, and the calcination is 4 h.

9. A three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the three-dimensional sandwich double-coated carbon mesh encapsulated hydrogenated titanium dioxide coated core-shell structure mesoporous ferrosoferric oxide composite material according to claim 9 in preparing negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of carbon-wrapped praseodymium-doped lithium iron phosphate composite positive material

    CN103165891A

  • Preparation method of three-dimensional ordered square-pore mesoporous carbon skeleton material

    CN105439121A

  • Preparation method of lithium nickel cobalt manganate composite material cladded with carbon-clad lithium iron phosphate

    CN107046130A

  • Double-shell-coated ferroferric oxide nano-particles as well as preparation method and application thereof

    CN113184915A

  • Preparation method and application of hydrogenated titanium dioxide modified core-shell structure porous ferroferric oxide and nickel oxide

    CN115472801A